Mapping of Reflective Thinking Levels and Basic Thinking Ability of Students on Learning Science at SMP Negeri 30 Sigi - Delviana, Delviana; Hamzah, Baharuddin; Solfarina, Solfarina (Universitas Tadulako, 2020)
This study aims to map the reflective thinking level of students and to map students' basic thinking skills in science learning at SMP Negeri 30 Sigi. The method used in this research is the descriptive method. The test used is a set of tests containing UN questions for the last five years about science learning given to students with the aim of obtaining information about students' basic thinking levels while measuring reflective thinking skills using a questionnaire that has been validated by experts. Students of SMP N 30 Sigi have very low basic thinking skills. The highest correct answer is 21 questions and the lowest correct answer is 7 questions. A total of 42 students as a whole had a reflective thinking stage for habitual action, 29 of which were transitions between habitual action and understanding, 11 of which were transitioning to habitual action, understanding, and reflective, and only 2 of them reached the critical thinking stage. Students 'reflective thinking skills are directly proportional to students' basic thinking skills. The higher the students 'reflective thinking stages, the better the students' basic thinking skills.